2008
DOI: 10.1021/la8025733
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanical Properties of a Polyglycerol Ester at the Air−Water Surface

Abstract: We studied the structure and mechanical properties of surface films resulting from the adsorption of a dispersed L beta phase at the air-water interface. This L beta phase corresponds to multilamellar vesicles and is formed by a commercial polyglycerol fatty acid ester (PGE) in aqueous solution at temperatures below the main chain-melting temperature (Tm=58 degrees C). We measured the adsorption kinetics using the pendant drop technique and mechanical properties of PGE films using oscillatory surface shear and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 26 publications
6
29
0
1
Order By: Relevance
“…This stabilizing force could be interpreted as a steric or structural repulsive force, which acts against forced film drainage as two bubbles are pressed against each other. As reported in an earlier article [16], PGE self-assembles at the air-water surface into a mesoscopic structure consisting of stacked mono-and bilayers. After sufficient adsorption time, this structure is no longer confined to the two-dimensional interface but extends into the surrounding bulk liquid (here: thin film).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…This stabilizing force could be interpreted as a steric or structural repulsive force, which acts against forced film drainage as two bubbles are pressed against each other. As reported in an earlier article [16], PGE self-assembles at the air-water surface into a mesoscopic structure consisting of stacked mono-and bilayers. After sufficient adsorption time, this structure is no longer confined to the two-dimensional interface but extends into the surrounding bulk liquid (here: thin film).…”
Section: Discussionsupporting
confidence: 57%
“…More details about the phase behavior and of the importance of residues of anionic fatty acid soaps are given elsewhere [15]. Recently, it was shown that despite the restricted molecular mobility in the gel-like state, PGE molecules are able to adsorb at the air-water interface at ambient temperature [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the foaming power is determined by the ability of PGE to adsorb at the newly created surface within equally short time scales. However, it has been recently shown that the adsorption kinetics of native solutions of this surfactant, at temperatures typical for processing, are very slow [18]. Yet in that article, the influence of the ion content of the solution on the adsorption kinetics was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Duerr-Auster et al, em 2008 tem relatado estudos sobre a estrutura e propriedades mecânicas de filmes superficiais resultado da adsorção ou dispersão de ésteres de poliglicerol (PGE) na interface ar-água através de métodos de reologia dilatacional e métodos oscilatórios de cisalhamento. Neste trabalho eles concluem que esses filmes moleculares são ativos na interface e possuem propriedades viscoelásticas provenientes da conectividade intermolecular de uma rede interfacial formada na monocamada, provavelmente devida à interações hidrofóbicas das cadeias alquílicas destes compostos (Duerr-auster et al, 2008). Anton, et al, em 2013 apresentaram um estudo que contribui grandemente ao melhor entendimento da reologia bi-dimensional das monocamadas de surfactantes não iônicos a base de polietilenoglicol (PEG) adsorvidos na interface óleo-água.…”
Section: Revisão Bibliográficaunclassified